Ordered Mesoporous C70 with Highly Crystalline Pore Walls for Energy Applications. (13th July 2018) - Benzigar, Mercy R.; Joseph, Stalin; Baskar, Arun V.; Park, Dae‐Hwan; Chandra, Goutam; Umapathy, Siva; Talapaneni, Siddulu Naidu; Vinu, Ajayan
Abstract: Mesoporous materials with carbon framework structure can offer distinctive functionalities with tunable electronic or catalytic properties. Many synthetic routes including hard or soft templating approaches are developed for the fabrication of various ordered mesoporous carbon based materials which have demonstrated unique catalytic and energy storage properties. So far, most of these techniques deliver only mesoporous carbon with amorphous wall structures which limit their performance in many applications. Fullerenes exhibit unique structure and significant properties including superconductivity, electrochemical stability, and heat resistance. Herein, for the first time, the preparation of highly ordered mesoporous fullerene C70 materials with tunable porous structure and controlled rod‐shaped morphology through the thermal oligomerization of fullerene C70 molecules inside the mesopore channels of SBA‐15 silica as a hard template with the help of chlorinated aromatics, wherein the solubility of fullerenes is high, is reported. It is demonstrated that these metal‐free mesoporous fullerene C70 framework with a high surface area and bimodal pores with multifunctionality exhibit excellent performance in the oxygen reduction reaction for fuel cells and supercapacitors. This simple strategy can also be extended to other fullerene nanostructures with different carbon atoms which can exhibit interesting physicochemical properties and find applications in catalysis and energy storage. Abstract : Highly crystalline metal‐free mesoporous fullerene C70 is prepared through combined strategy of nanotemplating and polymerization approaches. Their excellent performance in the oxygen reduction reaction with prominent four‐electron transport and high current density, comparable to that of Pt catalysts, is demonstrated and their excellent energy storage performance is also presented.